Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fnmol.2021.706494
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone Mitigates Enhanced Excitatory Neuronal Function and Repetitive Behavior Caused by an ASD-Associated Mutation of SIK1

Abstract: Six mutations in the salt-inducible kinase 1 (SIK1)-coding gene have been identified in patients with early infantile epileptic encephalopathy (EIEE-30) accompanied by autistic symptoms. Two of the mutations are non-sense mutations that truncate the C-terminal region of SIK1. It has been shown that the C-terminal-truncated form of SIK1 protein affects the subcellular distribution of SIK1 protein, tempting to speculate the relevance to the pathophysiology of the disorders. We generated SIK1-mutant (SIK1-MT) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Truncations of the SIK1 gene in two patients with infantile spasms occurred within a nuclear localization domain (NLD) in the C-terminal region [ 14 ]. We previously established a mouse line with a frame-shift mutation in the SIK1 gene that produces a truncated form of SIK1 protein and studied heterozygote SIK1-MT mice as models for human patients ( Figure 1 A) [ 15 ]. In this study, we analyzed male heterozygote SIK1-MT mice as models for DEE-30 and, hereafter, referred to them as SIK1-MT mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Truncations of the SIK1 gene in two patients with infantile spasms occurred within a nuclear localization domain (NLD) in the C-terminal region [ 14 ]. We previously established a mouse line with a frame-shift mutation in the SIK1 gene that produces a truncated form of SIK1 protein and studied heterozygote SIK1-MT mice as models for human patients ( Figure 1 A) [ 15 ]. In this study, we analyzed male heterozygote SIK1-MT mice as models for DEE-30 and, hereafter, referred to them as SIK1-MT mice.…”
Section: Resultsmentioning
confidence: 99%
“…SIK1 phosphorylates type II HDAC and removes it from MEF2. The C-terminal truncated form of SIK1 is unable to reside in the nucleus, therefore, it cannot activate the MEF2-mediated target gene transcription [ 14 , 15 , 25 , 32 ]. Cytosolic SIK1 phosphorylates CRTC, a coactivator for CREB [ 7 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risperidone and aripiprazole, the atypical antipsychotic drugs acting on the D2 dopamine receptor, have been approved to reduce irritability, agitation, aggression, and self-harm in ASD by the Food and Drug Administration (FDA) ( McCracken et al, 2002 ; Owen et al, 2009 ). Although risperidone has been reported to reduce RRBs in salt-induced kinase 1 (SIK1)-mutant mice via attenuating neural excitability and excitatory synaptic transmission ( Badawi et al, 2021 ), a meta-analysis published in 2020 showed that antipsychotics were not beneficial to RRBs in clinical trials ( Yu et al, 2020 ). Subsequently, another meta-analysis including more RCTs pointed out a slight improvement in RRBs after administration of antipsychotics ( Zhou et al, 2021 ).…”
Section: Treatment and Intervention Of Repetitive Restricted Behaviorsmentioning
confidence: 99%
“…Irrespective of the age of mice, patch-clamp recording from acute brain slices was performed as described previously [29,30]. Briefly, postnatal day 14-19 or postnatal day 35-40 the mice were shortly anesthetized with Isoflurane and decapitated.…”
Section: Electrophysiologymentioning
confidence: 99%